Leaching-Permeability Behavior of Collapsible Gypseous Soils Treated with Nano-Titanium Dioxide - Jassim, Najwa W.; Azmi, Mastura; Fattah, Mohammed Y. (Salehan Institute of Higher Education, 2025)
As a result of the limited studies that have been conducted on the utilization of nano titanium dioxide as a nanomaterial for stabilizing gypseous soils in geotechnical works, this study is directed to predict the changes in the coefficient of permeability k, the leaching strain, the total dissolved salts TDS, and the pH values with the changes in the percentages of nano titanium dioxide NTD. The gypseous soil samples were obtained from three sites located north of Baghdad, the capital of Iraq, with different gypsum contents of about 34%, 50%, and 60%. Tests have identified the mechanical and physical characteristics of the studied gypseous soils. In addition, oedometer permeability leaching tests were conducted using an oedometer cell apparatus. The results of the tested gypseous soils presented a significant effect of NTD on reducing the coefficient of permeability k and cost-effectively, especially at 0.3 and 0.5% for the three tested soils. For S1 tested soil, the reduction percentages of the k values were 79.02% and 80.0% when treated with 0.3% and 0.5% of NTD, respectively. While for S2 tested gypseous soil, the reduction percentages were 75.9% and 79.1%, and 66.04% and 73.6% for S3 tested gypseous soil when treated with 0.3% and 0.5% of NTD, respectively. The treated gypseous soils are exposed to less gypsum dissolution, as the NTD material forms an impermeable layer to prevent direct contact between water and gypsum. This reduces gypsum dissolution and, thus, reduces leaching strain. For S1 tested soil, the percentage of reduction of the leaching strain was 90.5%, while for S2 and S3 tested soils, it was 91.2% and 89.9%, respectively, when 0.3% of NTD was applied. As the percentage of the NTD increased for S1, S2, and S3, the pH values decreased due to decreased TDS in the leached water, and it is clear that 0.3% of NTD gives a reliable pH value for the three tested soils. Considering these results, it appears that even small amounts of nano titanium dioxide have the potential to be an effective agent for reducing permeability and stabilizing collapsible gypseous soils in civil engineering projects, compared with other nano or traditional materials.